Averaged Control for Fractional ODEs and Fractional Diffusion Equations. (17th July 2018) - Mitrovic, Darko; Novak, Andrej; Uzunović, Tarik
Abstract : We generalize results concerning averaged controllability on fractional type equations: system of fractional ODEs and the fractional diffusion equation. The proofs are accomplished by introducing appropriate Banach space in which we prove observability inequalities.